2011
DOI: 10.1029/2011je003848
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gravity waves on the Martian atmosphere: General circulation modeling

Abstract: [1] Our recently developed nonlinear spectral gravity wave (GW) parameterization has been implemented into a Martian general circulation model (GCM) that has been extended to ∼130 km height. The simulations reveal a very strong influence of subgrid-scale GWs with non-zero phase velocities in the upper mesosphere (100-130 km). The momentum deposition provided by breaking/saturating/dissipating GWs of lower atmospheric origin significantly decelerate the zonal wind, and even produce jet reversals similar to thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
152
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 101 publications
(171 citation statements)
references
References 52 publications
16
152
2
1
Order By: Relevance
“…The general altitude of the generators of the IAGWs needs to be fixed to evaluate the magnitude of the waves and the physics. The MGCM simulation to draw deep insight to the physical mechanisms of the gravity waves and their effects on the Martian thermosphere can be seen from previous studies (e.g.,Medvedev & Yiğit, ; Medvedev et al, ; Yiğit et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…The general altitude of the generators of the IAGWs needs to be fixed to evaluate the magnitude of the waves and the physics. The MGCM simulation to draw deep insight to the physical mechanisms of the gravity waves and their effects on the Martian thermosphere can be seen from previous studies (e.g.,Medvedev & Yiğit, ; Medvedev et al, ; Yiğit et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…This implies that nonsolar forcing is also important and may modulate or overwhelm the periodic solar forcing under certain conditions [e.g., Stewart , ]. This nonsolar forcing may be attributed to the impacts of upward propagating nonmigrating tides and gravity waves [ Stewart et al , ; Bell et al , ; Bougher et al , ; González‐Galindo et al , ; Medvedev et al , ; Medvedev and Yiğit , ; Stiepen et al , ]. Hence, the M‐GITM solar cycle variations presented in this paper should be used as baseline estimates.…”
Section: Discussionmentioning
confidence: 99%
“…The simulations with the Max Planck Institute Martian general circulation model (MPI-MGCM) showed that the GWs effects are significant above~100 km [Medvedev et al, 2011]. In addition, based on the simulations [Medvedev et al, 2011[Medvedev et al, , 2013 most of the cooling takes place at high latitudes and cannot be validated due to the insufficient coverage of the previous observations. All these facts imply that the neutral densities derived from the MGS/RS measurements be closer to the real neutral densities at 130 km in northern high latitudes (60°-90°N) than the simulation of the LMD MGCM(v4.3) model.…”
Section: Resultsmentioning
confidence: 99%
“…GWs generate by meteorological processes in the lower atmosphere, propagate upward, become unstable, and break and/or dissipate at higher altitudes, which transport momentum and energy and lead to a downward heat flux [Yiğit and Medvedev, 2015, and references therein]. The simulations with the Max Planck Institute Martian general circulation model (MPI-MGCM) showed that the GWs effects are significant above~100 km [Medvedev et al, 2011]. The simulations with the Max Planck Institute Martian general circulation model (MPI-MGCM) showed that the GWs effects are significant above~100 km [Medvedev et al, 2011].…”
Section: Resultsmentioning
confidence: 99%